2018
DOI: 10.1002/pbc.27356
|View full text |Cite
|
Sign up to set email alerts
|

Psychological risk in long‐term survivors of childhood acute lymphoblastic leukemia and its association with functional health status: A PETALE cohort study

Abstract: The results identified important functional health domains that could be targeted for interventions preventing psychological risk: vitality/fatigue, discomfort/symptoms, sleeping, and mental function issues. Health domains probably affect mood partly by limiting social/work/school functioning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 89 publications
(212 reference statements)
0
34
1
1
Order By: Relevance
“…A similar trend was seen for scoring moderate to extremely severe anxiety whereas levels of distress in YA ALL survivors and siblings were comparable. A prevalence for reporting depression, anxiety and stress in YA ALL survivors has been shown in studies from other contexts [10] and in comparison with siblings [40]. However, the levels of anxiety and distress found in our study were lower and were based on self-report rather than parent report.…”
Section: Discussioncontrasting
confidence: 71%
See 1 more Smart Citation
“…A similar trend was seen for scoring moderate to extremely severe anxiety whereas levels of distress in YA ALL survivors and siblings were comparable. A prevalence for reporting depression, anxiety and stress in YA ALL survivors has been shown in studies from other contexts [10] and in comparison with siblings [40]. However, the levels of anxiety and distress found in our study were lower and were based on self-report rather than parent report.…”
Section: Discussioncontrasting
confidence: 71%
“…While the long-term prevalence of physical health problems has been more widely investigated, knowledge on the long-term prevalence of mental health problems remains scarce. Results indicate a higher prevalence of mental ill health [8,9] poorer self-image [9] and mild to severe anxiety and depression [10]. There are however studies that have found the opposite, that ALL survivors report better HRQoL healthy controls of similar age [11].…”
Section: Introductionmentioning
confidence: 99%
“…The rates of neurocognitive deficits affecting executive function, processing speed and memory are threefold higher among survivors of childhood ALL than the general population (4,(6)(7)(8). Survivors also demonstrate behavioral and psychological problems (9)(10)(11), as well as worse academic performance (12,13).…”
Section: Introductionmentioning
confidence: 99%
“…We administered the translated versions of the 16D and 17D to two clinical samples, one being treated for PID, the other having recovered from pediatric cancer (Acute Lymphoblastic Leukemia (ALL)). These samples are drawn from larger studies (Abate et al, 2018 ; Anestin et al, 2018 ; Boulet-Craig et al, 2018 ; Lamore et al, 2020 ; Marcoux et al, 2017 ; Pépin et al, 2017 ; Sultan et al, 2017 ). Full sample description data are available in Tables S4-S5.…”
Section: Methodsmentioning
confidence: 99%
“…Full sample description data are available in Tables S4-S5. Descriptions of participants’ flow are available in the original study reports (Abate et al, 2018 ; Anestin et al, 2018 ; Boulet-Craig et al, 2018 ; Lamore et al, 2020 ; Marcoux et al, 2017 ; Pépin et al, 2017 ; Sultan et al, 2017 ). As we did not have hypotheses we did not calculate the required samples size.…”
Section: Methodsmentioning
confidence: 99%